Radicle emergence as a rapid indicator of sorghum seed vigor to predict mean germination time, vigor index, and field emergence - ADITYA KUSUMAWARDANA; SATRIYAS ILYAS; ABDUL QADIR; TRIKOESOEMANINGTYAS TRIKOESOEMANINGTYAS; SOERANTO HUMAN; SIHONO SIHONO (Asian Journal of Agriculture, 2026)
Abstract. Kusumawardana A, Ilyas S, Qadir A, Trikoesoemaningtyas, Human S, Sihono. 2026. Radicle emergence as a rapid indicator of sorghum seed vigor to predict mean germination time, vigor index, and field emergence. Asian J Agric 10 (1): g100124. https://doi.org/10.13057/asianjagric/g100124. This study aimed to develop a standardized radicle emergence test for sorghum (Sorghum bicolor) seeds by determining the optimal single-count timing and temperature for the simultaneous assessment of seed vigor and viability. This test was conducted by calculating the percentage of seeds whose radicles had emerged by at least 2 mm in length during a single observation period at the beginning of germination. Seed lots with low radicle emergence rates showed slow germination, reflecting an early physiological indicator of seed deterioration and a key factor contributing to reduced vigor. The experiment was arranged in a randomized complete block design with one factor: 12 sorghum genotypes, and four replications (blocks). Radicle length was measured at 2-h intervals from 40 to 48 h, with a minimum length of 2 mm. Results of radicle emergence (production of 2 mm radicle) at 25°C and alternating temperatures 20⇔30°C for 44 h (the optimal time), mean germination time, germination percentage, germination speed, vigor index, maximum growth potential, tetrazolium test, and field emergence were compared using 12 genotypes of sorghum seeds with standard germination above 83%. The single counts of radicle emergence performed at 25°C and 20⇔30°C were highly correlated with key vigor and viability indicators. Correlations with vigor-related traits, such as mean germination time (R²=0.87-0.81), vigor index (R²=0.83-0.89), germination speed (R²=0.73-0.71), and field emergence (R²=0.77-0.70), were strong, as were those with viability parameters, including standard germination (R²=0.66-0.59) and tetrazolium test results (R²=0.58-0.52). This study concludes that a single count of radicle emergence at 44 h, conducted at either 25°C or 20⇔30°C, is a method for simultaneous assessment of seed vigor (mean germination time, vigor index, germination speed, and field emergence) and viability in sorghum, offering a significant improvement over more time-consuming tests, such as germination test that requires 10 days.